Determinant factors of toothache in 8- and 9-year-old schoolchildren, Belo Horizonte, MG, Brazil - Eliane Paula Reis Barrêtto; Efigênia Ferreira e Ferreira; Isabela Almeida Pordeus (Sociedade Brasileira de Pesquisa Odontológica, 2009)
A cross-sectional study was carried out to determine the prevalence, severity and impact of toothache among schoolchildren associated with socio-demographic variables (gender, degree of maternal schooling, economic group, and oral health status). Six hundred and one 8- and 9-year-old children were randomly selected from schools in Belo Horizonte, MG, Brazil. After formal authorization was obtained from their parents, the children were interviewed and clinically examined by a single examiner. The Chi squared test was applied and the odds ratio obtained. The prevalence of toothache was 45.9% (276/601), of which 15.6% (94/601) had occurred during the previous month. Among the children who had experienced pain, 39.4% (109/276) classified its severity as intense or very intense. Nearly 35% (96/276) were awoken by the pain, and 63.8% (176/276) were unable to carry out daily tasks as a result. The prevalence of pain was greater among children from less privileged economic groups, in which the mothers' level of schooling was lower (0-7 years of formal study) and who showed poorer conditions of oral health, determined by the presence of dental and periodontal pathology (p<0.05). Gender did not influence either the experience of toothache or its severity and impact. The prevalence of toothache found in the age group between 8 and 9 years is very high and associated to social determinants and poorer conditions of oral health.